Essential oil and leaves from Lantana camara significantly ameliorate different cancer cell lines by suppressing the NF-κB pathway - Sajid, Arfaa; Manzoor, Qaisar; Sajid, Anam; Ahmad, Rabia Shabir; Hussain, Ghulam; Imran, Muhammad; Aslam, Farhan; Arshad, Muhammad Umair; Gondal, Tanweer Aslam; Imran, Ali (Penerbit Universiti Kebangsaan Malaysia, 2021)
The anticancer and anti-inflammatory activities of wild-sage (Lantana camara) leaves essential oil were evaluated against various human cell lines. In this regard, steam hydro-distillation technique was used for oil extraction. Chemical characterization of L. camara essential oil (LCEO) was done by GC-MS, and forty one chemical components (98.69%) were detected in leaves of LCEO. The major constituents were caryophyllene oxide (19.63%), caryophyllene (6.68%), β-phellandrene (6.48%), humulene epoxide II (5.68%), spathulenol (4.17%), α-pinene (3.27%), eucalyptol (3.09%), α-cyclocitral (2.89%), β-pinene (2.38%), and nerolidol II (2.33%). Moreover, the antioxidant and antimicrobial potential of LCEO were also examined. LCEO also showed good anti-inflammatory activity. Interestingly, it was found that the L. camara essential oil was active against a set of microbial strains along with promising antioxidant activity. The MTT assay showed that LCEO possessed good anticancer potential against U-266, A-549, HCT-116, SCC-4, MiaPaCa 2, and KBM-5 cancer cell lines. In these cell lines, it was depicted that the LCEO blocked the tumor cell proliferation via NF-κB pathway suppression. The promising and potent bioactivities of LCEO support the candidature of these essential oils as an anticancer agent.